Reversible Assembly of Microgels by Metallo‐Supramolecular Chemistry. Issue 18 (11th March 2020) - Es Sayed, Julien; Lorthioir, Cédric; Banet, Philippe; Perrin, Patrick; Sanson, Nicolas
Abstract: The combination of supramolecular chemistry and soft colloids as microgels represents an ambitious way to develop multi‐versatile colloidal assemblies. Hereafter, terpyridine‐functionalized poly( N ‐isopropylacrylamide) (PNiPAM) microgel building blocks are shown to undergo an assemble–freeze–disassemble process. The microgel assemblies, which are controlled by monitoring the attractive and repulsive potentials between the soft colloidal particles, are then frozen by forming inter‐particle metal–terpyridine bis‐complexes upon addition of the metallic cation (such as Fe II, Co II ). By oxidation of the metal–terpyridine bis‐complex links, the aggregates open up, which is due to the complex dissociation releasing the connected particles in the form of single microgels. We extended our work to the development of 1D filaments and 2D membranes materials made of soft particles connected via supramolecular chemistry. Abstract : Assemble–freeze–disassemble : Tailor‐made terpyridine‐functionalized PNiPAM microgels form a reversible supramolecular assembly. It freezes by formation of metallo‐supramolecular links between microgels, followed by oxidation‐responsive disassembly.